Regional Differences and Spatial-Temporal Evolution Characteristics of Digital Economy Development in China - Tong, Lei; Tang, Lu (Sustainability, 2025)
The digital economy, as an emerging productive force, has become a critical catalyst for economic sustainable progress. This study examines the regional disparities and origins of the digital economy, as well as its spatial and temporal growth patterns, which are essential for bridging the financial gap among regions and promoting synchronized economic progress. We developed a multidimensional index system to evaluate the level of digital economic development across 30 Chinese provinces, encompassing aspects such as the Internet’s evolution, digital infrastructure, capacity for digital innovation, and the application of digital technologies. The regional imbalances and origins of the digital economy were scrutinized using Dagum Gini coefficient decomposition. Furthermore, the study investigated the spatiotemporal dynamics of digital economy progression in China, employing methods like kernel density estimation, migration models of the gravity center, and an analysis via the standard deviation ellipse. The results reveal the following: (1) Digital economic development is more advanced in Eastern China compared to the western regions, with variations primarily driven by inter-regional differences. (2) The absolute gap in national digital economic development levels is widening, and relative disparities within the eastern region are increasing. Significant polarization is observed in the development of the digital economy across the central and western regions, while disparities in the northeastern region are comparatively minimal. (3) The center of gravity for China’s digital economy has overall shifted southward; the standard deviation ellipse has extended both northward and southward and become more oblate; and the dispersion within China’s digital economy has intensified.